Արեւմտահայ հոգեւորականութեան ու ժողովրդի հակազդեցութիւնը բողոքականութեան տարածմանը 1830—80-ական թթ - Բաբլումեան, Արփինէ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Деятельность американской миссионерской организации на территории Османской империи осуществлялась прежде всего среди армян. После принятия закона в 1850 г., когда протестанты были объявлены независимой общиной, численность армянской протестантской общины стало увеличиваться. Уже в 1860—1880-х гг. в различных населенных пунктах Западной Армении были созданы американские миссионерские станции со своими церквями, школами и последователь протестантами армянами. Увеличение числа армян-протестантов вызвало определенную неприязнь как среди населения, так и среди армянского духовенства. Реальное сопротивление распространению протестантизма было оказано со стороны Армянского Патриаршества в лице Патриархов Акопосa III и Матеоса II (далее — Католикос Всех армян Матеос I), кто проклял протестантов и исключил из Апостольской церкви. Противоречия имели ярко выраженные проявления и среди населения. The activities of the American missionary organization on the territory of the Ottoman Empire were carried out primarily among Armenians. After the adoption of the law in 1850, when Protestants were declared an independent community, the number of members of the Armenian Protestant community began to increase. Already in 1860—1880s, American missionary stations with their churches, schools and Protestant Armenians following them were established in various settlements of Western Armenia. The increase in the number of Protestant Armenians caused a certain dislike among both the population and the Armenian clergy. The real resistance to the spread of Protestantism came from the Armenian Patriarchs of Constantinople Hakobos III and Mattheos II, who anathematized Protestants and excluded them from the Apostolic Church. Protestant-apostolic contradictions had pronounced manifestations among the population as well.
Keywords: Կրօնագիտութիւն